Determinants of malnutrion in children aged 6-36 months - Linda Meliati; Mohammad Zen Rahfiludin; Apoina Kartini; Sutopo Patria Jati (AcTion: Aceh Nutrition Journal, 2025)
Stunting in children increases their risk of mortality, cognitive impairment, motor development, and poor body function. This study aimed to examine the relationship between low birth weight, low birth length, sex, age, and weight growth status and the prevalence of stunting, underweight, and wasting in children aged 6–36 months in West Lombok Regency, Indonesia. Methods: A cross-sectional study was conducted between November 2023 and May 2024 with 544 children. Secondary data were obtained from two community health centers in the study area. Data analysis was performed using the Spearman correlation test and chi-square test. Results: Birth weight and length were significantly associated with nutritional status in children. Higher birth weight was positively correlated with a better weight-for-age Z-score (WAZ; p = 0,001), height-for-age Z-score (HAZ; p = 0,009), and weight-for-height Z-score (WHZ; p = 0,0001), indicating a strong influence on overall growth and nutritional outcomes. Similarly, a greater birth length was significantly associated with WAZ (p = 0,0001), HAZ (p = 0,002), and WHZ (p = 0,006). Age was also correlated with HAZ (p = 0,005) and incidence of stunting (p = 0,0001), suggesting an age-related cumulative effect on linear growth. Moreover, children with low birth weight had a significantly higher risk of stunting (p = 0,0007), whereas those with low birth length were more likely to be underweight (p = 0,050). In conclusion, LBW and LBL are significant risk factors for stunting, wasting, and underweight in children aged 6–36 months in West Lombok Regency.